Analysis of Wireless Network Range In The Housing And Settlement Office of South Sumatra Province Based on Wifi Area Coverage - Imam Al Akbar (Institute of Information Technology and Social Science (IITSS), 2025)
WiFi technology widely used today is based on the IEEE 802.11a/b/g standard, which operates in the 2.4 GHz frequency band. This technology is commonly found in government institutions, private companies, entertainment centers, and educational environments. Wi-Fi (wireless fidelity) has become essential due to the increasing number of modern devices equipped with wireless capability, enabling unrestricted internet access within coverage areas. A field survey conducted at the Housing and Settlement Office of South Sumatra Province revealed that all computers rely on wireless connectivity; however, improper placement of access points has resulted in suboptimal network performance. This study aims to evaluate the range and quality of Wi-Fi signals in the office to improve wireless network accessibility. The research applies an action research methodology consisting of four stages: diagnosis, action planning, action taking, and evaluation. Findings indicate variations in signal strength and channel interference across rooms, highlighting the need for better access point placement and channel configuration.